HUBUNGAN PENDIDIKAN, PARITAS DAN UMUR IBU DENGAN KETIDAKPATUHAN KUNJUNGAN ANC DI PUSKESMAS PENYANDINGAN KABUPATEN OKU INDUK - Muryati Muryati; Eka Rahmawati; Yulizar Yulizar (Jurnal Ilmu Kebidanan, 2023)
Non-compliance in the ANC examination can cause the unknowability of various kinds of high-risk pregnancies that can affect the continuity of pregnancy or pregnancy complications so that they cannot be overcome immediately which will result in an increase in Maternal Mortality Rate (MMR). This type of research is observational research that is analytical in nature with a cross sectional design or approach. The sample in this study was 73 pregnant women who were and carried out examinations for pregnant women in the work area of the Puskesmas Penyandingan in 2023. The type of data used secondary data, The results of a bivariate study of the relationship between education, parity and maternal age with non-compliance of ANC visits based on the statistical test chi square education p-value 0.025 < 0.05, p-value parity 0.026 <0.05 and maternal age p-value 0.026< 0.05 can be concluded that there is a relationship between education, parity and maternal age simultaneously with non-compliance with ANC visits in the work area of UPTD Puskesmas Penyandingan Ogan Komering Ulu Induk Regency in 2022. The suggestion to the leadership of UPTD Puskesmas Penyandingan is to increase information about non-compliance with ANC visits by involving community leaders, health workers to provide counseling and counseling, as well as distributing brochures, billboards, and advertisements in print and electronic media so that the public knows the importance of ANC visits.